2020
DOI: 10.1016/j.molliq.2020.112827
|View full text |Cite
|
Sign up to set email alerts
|

Two fatty acid anion-based ionic liquids - part I: Physicochemical properties and tribological behavior as neat lubricants

Abstract: Two new ionic liquids ([N 6,6,6,6 ][C 8:0 ] and [N 6,6,6,6 ][C 16:0 ]) synthetized from fatty acids through a salt metathesis reaction were both characterized from a physicochemical and tribological point of view. Density, viscosity, corrosion activity and thermal stability tests were performed before making tribological tests under ball-on-disc both unidirectional (with fixed and variable slide-to-roll ratio) and reciprocating configuration. The main results of this work were the following: the longer the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…These properties were measured in the first part of this research [83], exhibiting the same behavior that other FAILs employed in previous research [84][85][86][87]. In addition, Table 1 shows density and viscosity values at reference temperatures (additional data can be found as Supplementary Information) of the blends resulting of mixing the FAILs at 0.5 and 2% in POE.…”
Section: Density and Viscositysupporting
confidence: 61%
See 2 more Smart Citations
“…These properties were measured in the first part of this research [83], exhibiting the same behavior that other FAILs employed in previous research [84][85][86][87]. In addition, Table 1 shows density and viscosity values at reference temperatures (additional data can be found as Supplementary Information) of the blends resulting of mixing the FAILs at 0.5 and 2% in POE.…”
Section: Density and Viscositysupporting
confidence: 61%
“…Besides, 1 H and 13 C nuclear magnetic resonance (NMR) and FTIR spectroscopy were executed to ascertain the chemical structure. The synthesis/identification procedure of these FAILs were described extensively in the first part of this research, as well as their density and viscosity data [83].…”
Section: Fatty Acid Anion-based Ionic Liquids (Fails)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic liquids (ILs) are organic salts with melting points below 100 °C which are endowed with unique physico-chemical properties such as low flammability, negligible vapor pressure, high thermal and chemical stability, and wide electrochemical window [ 24 , 25 , 26 , 27 , 28 ]. By careful selection of the constituting ions, the features of interest of an IL can be tailored to a given application.…”
Section: Introductionmentioning
confidence: 99%
“…They are made of natural-derived compounds, and their physical properties can be changed by manipulating their anion alkyl chain length. Longer anion alkyl chain length of fatty acid ionic liquids results in lower viscosity, density, water solubility (C 18 -stearate ionic liquid are not soluble in water), and corrosiveness as well as higher thermal stability [ 132 , 133 , 134 ]. Investigations indicated that the presence of hydroxyl group in the imidazolium cation part of fatty acid ionic liquids increased their thermal stability [ 132 ].…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%